Short-Term Fasting Selectively Influences Impulsivity in Healthy Individuals - Howard, Maxine; Roiser, Jonathan P.; Gilbert, Sam J.; Burgess, Paul W.; Dayan, Peter; Serpell, Lucy (Frontiers in Psychology, 2020)
Previous research has shown that short-term fasting in healthy individuals is associated with changes in risky decision-making. The current experiment was designed to examine the influence of short-term fasting in healthy individuals on four types of impulsivity: reflection impulsivity, risky decision-making, delay aversion, and action inhibition. Participants were tested twice, once when fasted for 20 hours, and once when satiated. Participants demonstrated impaired action inhibition when fasted; committing significantly more errors of commission during a food-related Affective Shifting Task. Participants also displayed decreased reflection impulsivity when fasted, opening significantly more boxes during the Information Sampling Task (IST). There were no significant differences in performance between fasted and satiated sessions for risky decision-making or delay aversion. These findings may have implications for understanding eating disorders such as Bulimia Nervosa (BN). Although BN has been characterised as a disorder of poor impulse control, inconsistent findings when comparing individuals with BN and healthy individuals on behavioural measures of impulsivity question this characterisation. Since individuals with BN undergo periods of short-term fasting, the inconsistent findings could be due to differences in the levels of satiation of participants. The current results indicate that fasting can affect performance on the IST, a measure of impulsivity previously studied in BN, whilst performance on other impulsivity measures were unaffected. However, the results from the IST were contrary to the original hypothesis and should be replicated before specific conclusions can be made.